PENYELESAIAN DEBITUR GAGAL: ANALISIS PADA KOPERASI SERBA USAHA TUNAS SEJAHTERA BURENGAN KEDIRI PERSPEKTIF HUKUM PERIKATAN - Aditya Rahman; Nichatus Sholikah; Sivanaya Nadila Putri; Muhammad Jazil Rifqi (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
In an agreement, of course, there are achievement that must be fulfilled by the debtor. But not infrequently there are problems in it. Non-performing financing is finacing for performance  that is jammed, doubtful, or substandard. This article aims to analyze cases of debtors who fail to pay at KSU Tunas Sejahtera and their settlements in various perspectives and various methods used in the settlement process. The method used by the author in preparing this article is descriptive qualitative, where the research is focused on examining the formulation of the problem and in-depth analysis based on various reference sources. In analyzing the settlement of this default debtor case, the authors use several perspectives, namely, the perspective of the debtor's legal engagement, the mediation perspective, the arbitration perspective, the default perspective, from the court's perspective. From the results of the study, the alternative implemented by KSU Tunas Sejahtera in solving problems is to carry out intensive billing, rescheduling, and reconditioning. Of the three alternative solutions above, Tunas Sejahtera KSU has not been able to resolve the problem, there are still many customers who fail to pay and customers are only able to pay half of the installments, namely 200-300 thousand including a 1.7% margin.